Effects of academic qualification on intra-professional conflict among nurses in South-East, Nigeria - Henrietta. A. RN, Okedo (International Journal For Research In Health Sciences And Nursing, 2024)
The observation of the researcher as a nurse in a hospital in South-East, Nigeria is to the effect that intra-professional conflict is rife among nurses. Strikingly, the incidence of intra-professional conflict among nurses could be a function of many factors among which are age and academic qualification. Thus, the purpose of this study was to investigate effects of academic qualification on intra-professional conflict among nurses in South-East, Nigeria. The research design employed in the study was a cross sectional survey, sample size of 997 nurses who were randomly selected participated in the study. The data were obtained using a 19-item questionnaire titled: Sources of Intra-Professional Conflicts among Nurses Questionnaire (SIPCNQ). SIPCNQ was validated by two other experts from nursing and health management. Reliability of SIPCNQ which was tested with Cronbach alpha test to determine its internal consistency obtained an alpha coefficient reliability of 0.68-0.86 and was considered reliable for the study. Mean, standard deviation and Analysis of Covariance (ANCOVA) were used for data analysis. The findings of the study revealed that intra-professional conflict negatively affected nurses with HND/other non nursing degrees the most, followed by nurses with BScN/BNSc degree while nurses with PGD/other diploma certificates are least affected by intra-professional conflict. Based on the findings of the study, it was recommended that nurses with lower academic qualification should work towards upgrading their qualification. That way, they will be more armed with vital information that border on intra professional conflict management.